Enhancement of Circulating and Intestinal T Regulatory Cells and Their Expression of Helios and Neuropilin-1 in Children with Inflammatory Bowel Disease - Sznurkowska K; Luty J; Bryl E; Witkowski JM; Hermann-Okoniewska B; Landowski P; Kosek M; Szlagatys-Sidorkiewicz A (Dove Medical Press, 2020)
Katarzyna Sznurkowska,1 Justyna Luty,2 Ewa Bryl,2 Jacek M Witkowski,3 Blanka Hermann-Okoniewska,4 Piotr Landowski,1 Marta Kosek,1 Agnieszka Szlagatys-Sidorkiewicz1 1Department of Pediatrics, Pediatric Gastroenterology, Allergology and Nutrition, Medical University of Gdańsk, Gdańsk, Poland; 2Department of Pathology and Experimental Rheumatology, Medical University of Gdańsk, Gdańsk, Poland; 3Department of Pathophysiology, Medical University of Gdańsk, Gdańsk, Poland; 4Department of Pathology and Neuropathology, Medical University of Gdańsk, Gdańsk, PolandCorrespondence: Katarzyna SznurkowskaDepartment of Pediatrics, Pediatric Gastroenterology, Hepatology and Nutrition, Medical University of Gdańsk, Nowe Ogrody 1-6, Gdańsk 80-803, PolandTel +58 663625861Fax +48 58 764 04 40Email k.sznurkowska@gumed.edu.plBackground/Aims: The proportions of intestinal and peripheral regulatory T cells (Tregs) in pediatric inflammatory bowel disease (IBD) were poorly investigated, as well as different subsets of these cells. Helios and Neuropilin-1 were proposed as markers differentiating between thymic and peripheral Tregs. Therefore, the aim of current work was to investigate the proportions of Tregs and expression of Helios and Neuropilin-1 in Tregs in peripheral blood and intestinal mucosa of children with inflammatory bowel disease.Materials and methods: Fifteen patients newly diagnosed with inflammatory bowel disease: ulcerative colitis (n=7) and Crohn’s disease (n=8) were included in the study. Nine children who presented with no abnormalities in colonoscopy served as a control group. Quantification of regulatory T cells of the CD4+CD25highFOXP3+ phenotype, as well as Helios+ and Neuropilin-1+ in peripheral blood and bowel mucosa was based on multicolor flow cytometry.Results: The rates of circulating and intestinal Tregs were significantly higher in the studied group than in the control group. The rate of intestinal T regulatory lymphocytes was significantly higher than circulating Tregs in patients with IBD, but not in the control group. The median proportion of circulating FOXP3+Helios+ cells amounted to 24.83% in IBD patients and 15.93% in the controls. The median proportion of circulating FOXP3+Nrp-1+ cells was 34.23% in IBD and 21.01% in the control group. No statistically significant differences were noted for the circulating FOXP3+Helios+ cells and FOXP3+Nrp-1+ cells between the studied and the control group.Conclusion: The rates of circulating and intestinal T regulatory cells are increased in naïve pediatric patients with IBD. The rate of Tregs is higher in intestinal mucosa than in peripheral blood in patients with IBD. Flow cytometry is a valuable method assessing the composition of infiltrates in inflamed tissue. Helios and Neuropilin-1 likely cannot serve as markers to differentiate between natural and adaptive Tregs.Keywords: T regulatory cells, circulating Tregs, intestinal Tregs, Helios, Neuropilin-1, IBD, inflammatory bowel disease, children